2022
DOI: 10.1186/s12913-022-07874-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hospital attributes on patient preference among outpatient attendants in Wolaita Zone, Southern Ethiopia: discrete choice experiment study

Abstract: Background Patient preference has preceded the use of health care services, and it has been affected by different hospital attributes. Meanwhile, the number of patients receiving vital health intervention is particularly low in Ethiopia. Therefore, this study aimed to determine the effect of hospital attributes on patient preference for outpatients in the Wolaita area in September 2020. Methods A discrete choice experimental study was applied to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Our work shows that these factors are highly valued by people. This result was consistent with previous studies (4, 1416, 18, 21, 22, 26, 48, 53, 69, 70). Of course, at the same time, we should also pay attention to the fact that some studies have shown that the competition of hospitals to use advanced facilities does not necessarily lead to an improvement in the quality of services or health outcomes (15, 7173).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Our work shows that these factors are highly valued by people. This result was consistent with previous studies (4, 1416, 18, 21, 22, 26, 48, 53, 69, 70). Of course, at the same time, we should also pay attention to the fact that some studies have shown that the competition of hospitals to use advanced facilities does not necessarily lead to an improvement in the quality of services or health outcomes (15, 7173).…”
Section: Discussionsupporting
confidence: 94%
“…Our study also pointed out the important role of provider competence and indicated that it played an important role in an individual’s choice preferences after hospital facilities. Previous studies also reported the significant role of “provider’s competency and skill” in choosing a hospital, and their result were consistent with the present study (1416, 22, 29). The provider’s competency depends on the knowledge, expertise, and skill of human resources of any organization.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations